Business Model in Action: Entrepreneurship Research (International Journal of Innovative Research in Engineering & Management, 2021)
Although the term "business model" is commonly used in the  industry, the scholarly book on the issue is fragmented and  complicated by various definitions and construct boundaries. In  this study, we review existing research and reconstruct the firm  model from an entrepreneurial standpoint. To help understand  how professional managers ensure concerning business  strategies, we provide us the findings of an applied linguistics of  151 surveys of practitioners and researchers. We determine that  the basic parameters of the financial model are capacity  organization, feedforward structure, and function of the number,  and we investigate the nature and effects of volumetric  dominance on corporate features and behavior. These findings  open up new paths for theoretically studies and subsequent study  in enterprise by relating the firm model to motivation,  opportunity cross, and work productivity.
Keywords: Business Model Cognition; Development; Empirical; Entrepreneurship